(untitled) (Cardiovascular Journal, 2010)
Conventional treatment of left main coronary artery (LMCA) disease includes coronary artery bypass graft (CABG) and more recently, in selective indications, percutaneous coronary intervention (PCI). Direct surgical patch angioplasty of the LMCA using fresh autologous pericardium, saphenous vein, or mammary artery patch can be proposed as an alternative treatment. We have successfully operated one patient with surgical angioplasty for isolated ostial left main coronary stenosis at National Heart Journal. Keywords: LMCA; PCI; Surgical angioplasty DOI: 10.3329/cardio.v3i1.6439 Cardiovasc. j. 2010; 3(1): 110-112